Mid-Upper Arm Circumference vs Body Mass Index in Association with Blood Pressure in Young Men: A Cross-Sectional Study - Wiwiek Fatchurohmah; Khusnul Muflikhah; Susiana Candrawati; Mustofa Mustofa (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Hypertension and obesity are major risks factor for cardiovascular disease (CVD), which is one of the leading causes of mortality. Many studies have shown that body mass index (BMI) and mid-upper arm circumference (MUAC) measurements are associated with blood pressure in children and adults. However, the association has not been studied extensively in young men. This study aims to investigate the correlation between BMI with blood pressure and MUAC and MUAC with blood pressure in young men. This is a cross-sectional study that consisted of 38 male participants who met the criteria. Blood pressure, BMI, and MUAC were measured using standard procedures. The mean of BMI, MUAC, systolic blood pressure (SBP), and diastolic blood pressure (SBP) was 24.68±4.41 kg/m2, 30.23±5.45 cm, 117.39±10.47 mmHg, and 75.57±8.44 mmHg, respectively. The Pearson correlation test between the BMI with SBP and BMI with DBP was statistically significant (p≤0.05) with r=0.446 and r=0.537, respectively. Contrarily, the MUAC and blood pressure show no significant association. This study concluded a moderate positive correlation of BMI with systolic and diastolic blood pressure in young men subjects.